Primary Intraoral Granulocytic Sarcoma: A Case Report and Review of Literature - Lamia Parveen; Sudeshna Bagchi; Rudra Prasad Chatterjee; Abdul Mahmud; Sangeeta Sinha (Indian Journal of Medical and Paediatric Oncology)
Granulocytic sarcoma (GS) is a rare extramedullary malignant tumor composed of immature granulocytes, including myeloblasts, promyelocytes, and myelocytes. In most cases, these are associated with persisting blood dyscrasias such as acute myeloid leukemia and chronic myeloid leukemia. To date, 32 cases of GS involving orofacial region have been reported in the English literature. Out of these, only a few presented without any systemic complications. This case reports an unusual occurrence of GS without any associated leukemia involving the mandible of a 29-year-old male patient. Hematoxylin and eosin–stained sections revealed the presence of numerous rounds to ovoid myeloblasts with a multilobated, vesicular nucleus and a prominent nucleolus. The cells stained positive for Cluster of Differentiation 68, lysozyme, and myeloperoxidase. He later underwent chemotherapy but succumbed in the interim period of chemotherapy. We hereby report a unique case of GS of mandible in an apparently healthy individual who deteriorated rapidly; an early and accurate diagnosis of which could have been life-saving.